Small‐Scale Discharges Observed Near the Top of a Thunderstorm - O. Scholten; B. M. Hare; J. Dwyer; N. Liu; C. Sterpka; J. Assink; H. Leijnse; S. ter Veen (Geophysical Research Letters, 2023)
Abstract We have used the LOw‐Frequency ARray (LOFAR) to image a few lightning flashes during a particularly severe thunderstorm. The images show an exceptional amount of VHF activity at altitudes above 10 km. Much of this is in the form of small‐scale discharges, not exceeding a few hundred meter, occurring seemingly randomly around the centers of active storm cells. To emphasize the incidental nature of these small‐scale discharges or sparks we refer to them as “sparkles.” A detailed investigation shows evidence that these sparkles are indicative of positive leader channels and that they are equivalent to the needle activity seen around positive leader tracks at lower altitudes.